2021
DOI: 10.1049/gtd2.12115
|View full text |Cite
|
Sign up to set email alerts
|

Stacked denoising autoencoder based fault location in voltage source converters‐high voltage direct current

Abstract: High voltage direct current has been more and more popular in modern transmission systems. Accurate fault location could help fault clearance and fast recovery of the faulted system. A stacked denoising autoencoder based fault location method for high voltage direct current transmission systems is proposed. The local measurements are analysed, and an end-to-end stacked denoising autoencoder-based fault location is realised. Representative features are extracted with unsupervised learning and labelled as the in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…Researchers used the unsupervised learning method for fault extraction trained later. Final results showed that it can accurately locate fault in various situations, making the fault system recover faster [9] . Li h et al found that the lack of damage labels made it difficult for the existing deep neural network to carry out effective damage detection.…”
Section: Related Workmentioning
confidence: 96%
See 1 more Smart Citation
“…Researchers used the unsupervised learning method for fault extraction trained later. Final results showed that it can accurately locate fault in various situations, making the fault system recover faster [9] . Li h et al found that the lack of damage labels made it difficult for the existing deep neural network to carry out effective damage detection.…”
Section: Related Workmentioning
confidence: 96%
“…There are linear, polynomial, radial basis, and sigmoid function. Sigmoid function is selected as the model kernel function in equation (9).…”
Section: Iei Teaching Quality Evaluation Model Construction By Adapti...mentioning
confidence: 99%
“…Numerous studies have attempted to employ machine learning techniques for HVDC system failure detection, as advancements in statistics and machine learning technology continue to progress [8,9]. In reference [10], the characteristics of DC voltage and DC current are extracted using principal component analysis (PCA), and then these features are trained and tested using support vector machine (SVM) for fault identifcation and classifcation.…”
Section: Introductionmentioning
confidence: 99%